VARIAÇÃO NO USO DO INFINITIVO PESSOAL - Gorski, Edair (Organon, 2012)
This paper investigates the variable use of the infinitive in oralBrazilian Portuguese considering both the verb morphology and the formalrepresentation of the subject. The analysis of sociolinguistic interviews shows thatthe speakers prefer both the non-finite verb form of the infinitive (92%) and nosubject expressed (71%). These results display a tendency for a regularization ofthe infinitive as an impersonal form. Empirical results also point out a correlationbetween finite verb form and formal representation of the subject, which are highlymarked constructions. The independent variables subject coreferentiality, semantic(in)determination of the subject and syntactic coding of the clause are statisticallysignificant for the expression of the subject.